Building Intellectual Humility Among Employees in Dr. Obote College School - Joyce Apio (Uganda Christian University, 2026)
The study aimed at exploring building intellectual humility among employees in Dr. Obote College School. It specifically focused on: providing a justification for intellectual humility among employees, examining the awareness and exhibition of intellectual humility among employees, and exploring the mechanisms for fostering intellectual humility among employees in Dr. Obote College School. This research study used the constructivist version of a grounded theory approach to explore ways through which intellectual humility can be built among employees at Dr. Obote College School. Participants were selected by purposive sampling from among administrators, teachers, and nonteaching staff until data saturation was achieved. Data were collected through semi-structured interviews, while analysis, concurrently done with data collection, involved coding, memoing, constant comparison, and theoretical sampling to generate a substantive model. Quality standards are guaranteed through measures of credibility, transferability, dependability, and confirmability, while ethical considerations, such as informed consent, confidentiality, and voluntary participation, are strictly upheld. The research findings indicated that intellectual humility at Dr. Obote College School promotes staff performance, teamwork, decision-making, and professional relationships, although awareness of the concept is generally low among junior and non-teaching staff. The employees showed that humility through assist-searching for, comments reception, and admiration for others; that is cultivated by way of the school through conferences, open-door management, mentorship, professional improvement, inclusive decision-making, and a deferential lifestyle that values reflection. The respondents also emphasized that education in based codecs can be necessary, alongside more potent mechanisms for giving and receiving remarks, popularity mechanisms, and embedding humility into school values for the total institutionalization of humble practices. Finally, the study recommends that developing intellectual humility at Dr. Obote college college be finished via based workshops in capability constructing, more potent mechanisms for remarks, increasing mentorship packages, consultative selection-making, and embedding humility into the center values of the college and its structures for reputation so that you can nurture self-focus, collaboration, non-stop studying, and a tradition of mutual respect.